The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jafrearsci.2014.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Gravimetric evidences of active faults and underground structure of the Cheliff seismogenic basin (Algeria)

Abstract: International audienceThe Cheliff basin (ex El Asnam) is known as one of the most seismic active zone in Algeria and the West Mediterranean region. We can cite the El Asnam earthquake which occurred in 10.10.01980 with magnitude of 7.3. It was generated by a thrust fault with NE–SW sinistral component. Until now, there is a little information about existence of deep active faults, which generate this strong activity. The gravity field is an important resource of information on crustal structure. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…Whereas many others complete the structural information. There is also a good correlation with other geophysical and geological studies (Ouyed et al, 1983;Meghraoui, 1988;Avouac et al, 1992;Bezzeghoud et al, 1995;Aifa et al, 2003;Afalfiz et al, 2009;Beldjoudi et al, 2012;Abtout et al, 2014).…”
Section: Accepted Manuscriptsupporting
confidence: 71%
See 3 more Smart Citations
“…Whereas many others complete the structural information. There is also a good correlation with other geophysical and geological studies (Ouyed et al, 1983;Meghraoui, 1988;Avouac et al, 1992;Bezzeghoud et al, 1995;Aifa et al, 2003;Afalfiz et al, 2009;Beldjoudi et al, 2012;Abtout et al, 2014).…”
Section: Accepted Manuscriptsupporting
confidence: 71%
“…As this anomaly remains negative, its origin is in the Palaeozoic substratum which is more magnetized and deepest than the Cretaceous one. This is also confirmed by the identification of the sources of the magnetic anomalies in 2-D along the profile and in 3-D (see section 6, below) and by the gravity study of the same area (Idres et al, 1998;Abtout et al, 2014) Some contacts are identified on the gradient map ( Figure 5). The NW-SE one is thrusting in the sinistral way the Boukadir anomaly.…”
Section: Description Of the Aeromagnetic Field Mapssupporting
confidence: 57%
See 2 more Smart Citations
“…Eventual seismic and well data are available but belong to mining and oil companies. Several studies such as Asfirane and Galdeano (1995), Idres (1983), Bournas et al (2003), Abtout et al (2014), Meliani et al (2016) and Boukerbout et al (2018) used gravity and magnetic data (with eventual further processing showing main buried fault directions, main source depths, etc.) to investigate deep crustal structure, but numerical modeling lacks.…”
Section: Introductionmentioning
confidence: 99%